KONSEP DAN POLA ASUH ORANG TUA TERHADAP PEMBENTUKAN KARAKTER ANAK DALAM PERSPEKTIF ISLAM (QS : LUKMAN AYAT 12-19) - Iwan Ridwan (Universitas Sultan Ageng Tirtayasa, 2019)
AbstractCharacter building that is illustrated by the Qur'an with various examples should be able to answer various problems of character education that affect people at this time, such as moral education and worship. Lukman was made Allah in the Qur'an as a wise person and a pious person and succeeded in educating his son to be a complete Muslim person, therefore the purpose of this article is to; First: knowing important aspects that are the center of attention of Lukman Hakim in the process of his children's education, Second: Lukman Hakim's strategy in carrying out education, Third: The concept of children's character education based on the Qur'an. This research uses the library research method (Library Research), or library research by searching, gathering, reading, and analyzing books, which have relevance to the research problem. Then processed according to the ability of the author. The type of research in writing this research report is qualitative research. After the authors obtain relevant references, then the data is compiled and analyzed so that it gets a conclusion. Keyword: Parenting, Character Building, Lukman al-Hakim